The Effectiveness of the Effleurage Massage Method Compared with Rubbing Massage on Reducing the Intensity of Normal Labor Pain in the First Active Phase - Meidayana Refisiliyani; Riu, Deviana Soraya; Usman, Andi Nilawati (Window of Health : Jurnal Kesehatan, 2023)
Labor pain is a physiological journey experienced by a woman to gain a subjective experience of physical feelings related to uterine contractions, cervical dilatation and effacement, and fetal descent during labor. This study aims to determine the effectiveness of the effleurage massage method compared to rubbing massage in reducing the pain intensity of normal labor during the first active phase. This type of research uses Quasi-Experimental with a Pretest-Posttest with a control group design. The population consisted of 45 respondents divided into three groups: two intervention groups and one control group. Each group consists of 15 respondents, selected through a total sampling technique. The use of an observation sheet that contains a list of observed points by marking the numbers contained in the assessment sheet, which shows the level of pain that the mother feels and is applied before and after the intervention is used as an indicator in measuring the effectiveness of the two methods using the Visual Analogue Scale (VAS) measurement scale. Data were analyzed using the Wilcoxon Test, the Kruskal-Wallis Test, and the Mann-Whitney Test. The results showed that the group given effleurage massage experienced a decrease in labor pain intensity by 12 respondents (80%) with a p-value of 0.000, and the group given rubbing massage experienced a decrease in labor pain intensity by ten respondents (66.7%) with a p-value value 0.000 while the comparison between the effleurage massage and rubbing massage groups obtained a p-value of 0.417 > 0.05. So that the use of pain reduction methods such as non-pharmacological methods in the form of effleurage massage and rubbing massage is always expected to be an option for health workers, in this case midwives in the handling of mothers in childbirth, considering that many factors influence the perception of pain which are very subjective and individual.